JAMINAN JANGKA WAKTU PENGGUNAAN LAHAN DAN DAYA TARIK INVESTASI PERKEBUNAN SKALA BESAR: TELAAH PUSTAKA DARI PERSPEKTIF EKONOMI - Loso Judijanto; Al-Amin (Adisam Publisher, 2025)
This study discusses the relationship between land tenure security and investment attractiveness in large-scale plantation sectors from an economic perspective using a literature review method. Legal certainty regarding land tenure is a key determinant in shaping a stable investment climate, given the long-term, capital-intensive nature of plantation investments and the relatively long payback period required. The literature review findings indicate that certainty regarding the duration of land use rights not only reduces legal and social uncertainty risks but also enhances investor confidence and promotes efficiency in resource management. On the other hand, investment attractiveness is also significantly influenced by economic factors such as commodity price stability, infrastructure availability, government policy incentives, value chain integration, and compliance with environmental sustainability and social responsibility principles (ESG). The findings of this study emphasise the importance of synergy between legal policies and economic strategies so that large-scale plantation investments can provide optimal benefits for national economic development, environmental protection, and community welfare.